2012
DOI: 10.3389/fphys.2012.00177
|View full text |Cite
|
Sign up to set email alerts
|

Decompression vs. Decomposition: Distribution, Amount, and Gas Composition of Bubbles in Stranded Marine Mammals

Abstract: Gas embolic lesions linked to military sonar have been described in stranded cetaceans including beaked whales. These descriptions suggest that gas bubbles in marine mammal tissues may be more common than previously thought. In this study we have analyzed gas amount (by gas score) and gas composition within different decomposition codes using a standardized methodology. This broad study has allowed us to explore species-specific variability in bubble prevalence, amount, distribution, and composition, as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 58 publications
1
22
0
Order By: Relevance
“…Carbon dioxide, on the other hand, is produced by aerobic metabolism and may accumulate to high levels in metabolically active tissues. Local accumulation, and high diffusivity of CO 2 may form bubble precursors that continues to grow from N 2 diffusion (Harris et al, 1945; Behnke, 1951; Bernaldo De Quirós et al, 2012, 2013). Even though the carbonic anhydrase enzyme system might dissolve such bubble precursors quickly, they might still trigger bubble formation in N 2 -supersaturated tissue.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Carbon dioxide, on the other hand, is produced by aerobic metabolism and may accumulate to high levels in metabolically active tissues. Local accumulation, and high diffusivity of CO 2 may form bubble precursors that continues to grow from N 2 diffusion (Harris et al, 1945; Behnke, 1951; Bernaldo De Quirós et al, 2012, 2013). Even though the carbonic anhydrase enzyme system might dissolve such bubble precursors quickly, they might still trigger bubble formation in N 2 -supersaturated tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Once the dissolved tissue gas tension (P tiss ) exceeds the ambient pressure (P amb ), the tissue is supersaturated, and bubbles may form. The bubbles are believed to be the instigator for decompression sickness (DCS) symptoms seen in human divers, or gas bubble emboli found in marine mammals (Moore et al, 2009; Bernaldo De Quirós et al, 2012; Dennison et al, 2012). Scholander (1940) hypothesized that the unusual respiratory system in marine mammals, with a stiff trachea and rather compliant chest, allows the alveoli to collapse at shallow depths, thereby limiting the uptake of inert gas, reducing the level of N 2 that would be taken up during a dive and therefore reducing the likelihood of gas bubble emboli in breath-hold diving mammals.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, necropsy reports from mass stranded whales indicated DCS-like symptoms (Jepson et al, 2003;Fernández et al, 2005). A more recent study has shown that the gas bubble composition in stranded whales is similar to that from land mammals suffering DCS in experimental dive models (Bernaldo De Quirós et al, 2012). Imaging work in both live and stranded marine mammals indicates that they live with elevated inert gas tensions that cause bubbles to form under certain circumstances (Dennison et al, 2012).…”
mentioning
confidence: 99%